The Global Compact and Gender Inequality: A Work in Progress. (March 2013) - Kilgour, Maureen A.
A number of international organizations have identified eliminating gender inequality as a critical element in poverty reduction and development. Given that the Global Compact (GC) was launched, in part, to work toward the achievement of these goals, this article argues that the GC should pay significant attention to gender inequality in its learning network. The article discusses the findings of a review of the GC learning network, which reveals that the issue of gender inequality was missing from its agenda in its first decade. The author suggests explanations for this finding, including the lack of participation by women's organizations in the GC learning network, the lack of a gender discourse in corporate social responsibility initiatives generally, and the GC's focus on the business case, which may deflect attention from gender inequality where no clear business case can be made.